La enseñanza tradicional de las ciencias versus las nuevas tendencias educativas - Torres Salas, María Isabel (Revista Electrónica Educare, 2010)
To think of an educational proposal that teaches how to learn, it is necessary to consider a change not only educationally but also political, social, economical, ecological, cultural, among others, to enable an understanding of reality and in which there can be a construction of knowledge and a crucial role of sciences. But we must not forget that the development of science has been marked by the so-called positivistic science that it is characterized by interpreting phenomena and how this function through theories and laws, where the context and humans have a very poor leading role, if any, to which one can call scientism, which has allowed development even above human needs. However, since the 90s, there is a resurgence of progressive humanism in the educational fields, where there is a search of a revaluation of what it is considered human, which involves a series of epistemological and methodological changes that drives us towards new ways of working. This calls us to reflect on extreme choices to build knowledge, beyond the traditional teaching of the sciences, which are comprehensive, systematic, and flexible and rooted in a humanistic culture. Some models of the new trends are: directed research, discovery learning, inquiry learning and teaching of science and new technologies.